Analisis Hubungan Dukungan Keluarga dengan Kepatuhan Minum Obat Pasien Hipertensi - Febriyanti Zulyani; Tafia Inayah; Sri Mukti Suhartini (Jurnal Pendidikan Indonesia, 2026)
Hypertension is a non-communicable disease with a high prevalence that requires long-term management, including adherence to medication therapy. The 2023 Indonesian Health Survey (SKI) reported that 34.11% of the Indonesian population had hypertension. According to the Depok City Health Office (2024), the number of individuals with hypertension in Depok City reached 152,907. However, the level of adherence to antihypertensive medication in Depok remains relatively low, with only 45.9% of patients adhering to their prescribed medication regimen. This study aimed to determine the relationship between family support and medication adherence among hypertensive patients at Beji Community Health Center (Puskesmas Beji). The study employed a correlational analytic design with a cross-sectional approach, using a consecutive sampling technique. Data were collected using the 8-item Morisky Medication Adherence Scale (MMAS-8) and a modified Family Support Questionnaire based on Toulasik’s Likert scale. The data were analyzed using the chi-square test. The results showed that most patients had good family support and a relatively high level of medication adherence. However, statistical analysis yielded a p-value of 0.752, indicating that there was no significant relationship between family support and medication adherence among hypertensive patients at Beji Community Health Center. Therefore, it can be concluded that family support was not significantly associated with medication adherence among hypertensive patients at Beji Community Health Center.